2019
DOI: 10.1128/jvi.01189-18
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir Monotherapy of Simian Immunodeficiency Virus-Infected Macaques Selects for Several Patterns of Resistance Mutations with Variable Virological Outcomes

Abstract: Drug resistance remains a major concern for human immunodeficiency virus (HIV) treatment. To date, very few resistance mutations have emerged in first-line combination therapy that includes the integrase strand transfer inhibitor (INSTI) dolutegravir (DTG). In vitro, DTG selects for several primary mutations that induce low-level DTG resistance; secondary mutations, while increasing the level of resistance, however, further impair replication fitness, which raised the idea that DTG monotherapy may be feasible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In agreement with this hypothesis, all insertions reported to date also contained the small amino acid glycine (G), which could contribute to loop flexibility. Importantly, in our study, insertions could be found in circulating strains as well as proviruses, indicating that both replicative capacity and integration were conserved [5]. The replicative competence of retroviruses carrying integrase insertions is now confirmed by Le Hingrat et al's report of evolution from 2 to 5 amino acid insertions in 1 patient [1].…”
Section: Insertion As a Resistance Mechanism Against Integrase Inhibisupporting
confidence: 74%
See 2 more Smart Citations
“…In agreement with this hypothesis, all insertions reported to date also contained the small amino acid glycine (G), which could contribute to loop flexibility. Importantly, in our study, insertions could be found in circulating strains as well as proviruses, indicating that both replicative capacity and integration were conserved [5]. The replicative competence of retroviruses carrying integrase insertions is now confirmed by Le Hingrat et al's report of evolution from 2 to 5 amino acid insertions in 1 patient [1].…”
Section: Insertion As a Resistance Mechanism Against Integrase Inhibisupporting
confidence: 74%
“…The insertion consisted of 5 amino acids after position 232 in the integrase of SIVmac251, and could not be introduced in either SIVmac239 or HIV-1 without severely impairing fitness [4]. More recently, we also reported the frequent emergence of various 5 or 6 amino acid insertions in the SIVmac251 integrase in rhesus macaques treated with dolutegravir monotherapy [5]. Integrase insertions in this setting were heterogeneous in sequence, but all contained 2 positively charged amino acids, and all were found in the immediate vicinity of arginine (R) 231, a residue that was shown by cryogenic electron microscopy (cryo-EM) to be the only one outside of integrase catalytic domain to interact with host target DNA strongly [6].…”
Section: Insertion As a Resistance Mechanism Against Integrase Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, we present a unique instance of de novo selection of Env mutations that confer resistance to DTG in vitro. Ongoing studies should determine whether the Env mutations described here confer resistance to other classes of ARVs, and whether mutations in Env can contribute to escape from ARV therapy in infected individuals (86). The results of this work will provide fundamental insights into mechanisms of drug resistance and viral spread in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…These antiretroviral drugs were administered in a formulation of a 3-drug cocktail dissolved in the vehicle kleptose following previously published doses for each drug. Each milliliter of formulation contained the reverse transcriptase inhibitors PMPA (20 mg/mL) (50-52) and FTC (30 mg/mL) (53) and the integrase inhibitor DTG (2.5 mg/mL) (54,55).…”
Section: Methodsmentioning
confidence: 99%